1998
DOI: 10.1046/j.0909-8836.1998.eos106307.x
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of CSF‐1 and its inhibition in rat dental follicle cells, implications for tooth eruption

Abstract: Tooth eruption requires the presence of a dental follicle around the unerupted tooth. Before the onset of eruption there is an influx of mononuclear cells into the follicle which, in turn, form osteoclasts that erode the alveolar bone. Eruption can be accelerated by the injection of colony-stimulating factor-one (CSF-1), a molecule that is maximally transcribed and translated in the dental follicle cells at the time of peak influx of mononuclear cells into the follicle of the rat first mandibular molar. To det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…As seen by the results discussed above, both CSF‐1 and PTHrP reduce the secretion of OPG in vitro and can do so at the same concentration that maximally reduces the expression of OPG in vitro (4). CSF‐1 is secreted by the dental follicle cells (9, 18) and, as such, could have an autocrine effect on the cells to inhibit OPG secretion. Because the CSF‐1 gene is maximally expressed in the follicle of the first mandibular molar at day 3 postnatally in the rat, it is probable that maximal secretion of CSF‐1 occurs to contribute to the reduction in OPG expression also seen at day 3 postnatally (4).…”
Section: Discussionmentioning
confidence: 99%
“…As seen by the results discussed above, both CSF‐1 and PTHrP reduce the secretion of OPG in vitro and can do so at the same concentration that maximally reduces the expression of OPG in vitro (4). CSF‐1 is secreted by the dental follicle cells (9, 18) and, as such, could have an autocrine effect on the cells to inhibit OPG secretion. Because the CSF‐1 gene is maximally expressed in the follicle of the first mandibular molar at day 3 postnatally in the rat, it is probable that maximal secretion of CSF‐1 occurs to contribute to the reduction in OPG expression also seen at day 3 postnatally (4).…”
Section: Discussionmentioning
confidence: 99%
“…Cells within the dental follicle region, a loose connective tissue surrounding the developing tooth, play a critical role in the process of tooth eruption (17–22) . In addition, substantial evidence exists indicating that follicle cells are progenitors of periodontal cells including cementoblasts, PDL fibroblasts, and alveolar osteoblasts (23–25) .…”
Section: Introductionmentioning
confidence: 99%
“…Mononuclear and osteoclast formation initiate at day 3 postnatally in the rat molar . Highly-expressed molecules, such as CSF-1, EGF, MCP-1 and NF-КB, have all been proven significant in the ostoclastogenesis process during eruption (Lin et al, 1996;Grier et al, 1998;Que et al, 1998;Que et al, 1999). However, relatively few in vivo studies have been carried out on the role of those molecules in osteogenesis during eruption.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that vascular endothelial growth factor (VEGF), dexamethasone/insulin, bone morphogenetic protein 2 (BMP2) and bone morphogenetic protein 7 (BMP7) can promote cementoblast/osteoblast differentiation of DFCs (Zhao et al, 2002;Morsczeck et al, 2005;Chen et al, 2007;Kémoun et al, 2007). In tooth eruption, cytokines such as colony-stimulating factor 1 (CSF-1) and its receptor, interleukin-1 (IL-1) and its receptor, endothelial growth factor (EGF), monocyte chemoattractant protein 1 (MCP-1) and nuclear factor-κB (NF-κB) were noted for their involvement in the dental follicle, in which they combine to form a complicated tooth eruption network system (Lin et al, 1996;Wise et al, 1997;Xu et al, 1998;Que et al, 1998;Grier et al, 1998;Que et al, 1999;Gu et al, 2003).…”
Section: Introductionmentioning
confidence: 99%